Middle Triassic to Late Jurassic climate change on the northern margin of the South China Plate: Insights from chemical weathering indices and clay mineralogy - Dai, Xianduo; Du, Yuansheng; Ziegler, Martin; Wang, Chaowen; Ma, Qianli; Chai, Rong; Guo, Hua (Palaeogeography, palaeoclimatology, palaeoecology, 2022)
The early Mesozoic greenhouse period was characterized by variable climate conditions. The driving mechanisms of this long-term variability are unclear due to a lack of full-period climate reconstructions. In particular, reconstructions of the terrestrial environment are rare, especially reconstructions representing South China during the early Mesozoic period. We focused on the major, trace and rare earth element compositions and clay mineralogy of 173 mudstones from the northern margin of the South China Plate. These data were used as proxies to evaluate the weathering intensity and reconstruct the climate variability from the Middle Triassic to the Late Jurassic after considering the potential effects of provenance, diagenesis and sedimentary sorting and recycling. From the latest part of the Triassic to the early Middle Jurassic, five well-correlated chemical weathering indices, the chemical index of alteration (CIA), chemical index of weathering (CIW), plagioclase index of alteration (PIA), sodium depletion index (τNa) and weathering index of Parker (WIP), imply an advanced degree of chemical weathering (e.g., CIAcorr, the corrected CIA, ranging from 71.1 to 88.0) and a clay mineral assemblage zone with abundant kaolinite. Together, these findings indicate a dominant humid climate. In the pre-Late Triassic and post-Middle Jurassic, the dominant seasonally arid climate was characterized by low and widely variable chemical weathering index values (e.g., CIAcorr values of 59.4–85.4) and clay mineral assemblage zones containing chlorite, smectite and mixed-layer illite–smectite but less kaolinite. We suggest that PCO2 variations, the megamonsoon effect, plate motion and regional topography all contributed to the observed climate changes during the early Mesozoic. •Early Mesozoic terrestrial climate change on the South China Plate was revealed.•A seasonally arid climate prevailed pre-Late Triassic and post- Middle Jurassic.•The humid climate of the Late Triassic–Early Jurassic interrupted this arid climate.•PCO2, a megamonsoon, plate motion and topography jointly controlled climate change.